An unforgettable journey in Romania (Confluenţe Bibliologice, 2016)
The article presents tourist and historical sights, natural landscapes, spectacular places from Romania. Romania hides natural wonders, monuments, places of worship, landforms and mysterious places that deserve to be visited and discovered. Discover Romania, a country with fairy tale scenery!
Keywords: international projects; architectural landmarks of Romania